Analisa Kombinasi Algoritma Burrows Wheeler Transform dan Adaptive Huffman Coding untuk Kompresi Citra - Gusron Hasibuan (Bulletin of Multi-Disciplinary Science and Applied Technology, 2022)
Image is one of the tools that humans use to convey messages to other humans. Image has developed along with the development of human civilization. Combination of Burrows Wheeler Transform (BWT) with Adaptive Huffman Coding (AHC) The process of Adaptive Huffman Coding Algorithm is reading one by one from the leftmost character to the end, it will change the initial character data using Burrows Wheeler Transform to change the order of the character set to be read by Adaptive Huffman Coding. This aims to compress the image by combining the Burrows Wheeler Transform method and the Adaptive Huffman Coding Algorithm to make the image file capacity small so that it can save storage media and is not slow when sending images from one place to another. Compression results depend on the selection of the desired compression quality. If you choose compression with standard quality, then the compressed image with the original image will not see the difference, but the reduction in bytes size is not too drastic. But if we choose a low compression quality, then the size of the bytes in the image will be reduced but the quality of the compressed image will be visible the difference with the original image.